Immunization with the Recombinant Cholera Toxin B Fused to Fimbria 2 Protein Protects against Bordetella pertussis Infection - Olivera, María Noelia (2014)
This study examined the immunogenic properties of the fusion protein fimbria 2 of Bordetella pertussis (Fim2)—cholera toxin B subunit (CTB) in the intranasal murine model of infection. To this end B. pertussis Fim2 coding sequence was cloned downstream of the cholera toxin B subunit coding sequence.Theexpression and assembly of the fusion protein into pentameric structures (CTBFim2) were evaluated by SDS-PAGE and monosialotetrahexosylgaglioside (GM1-ganglioside) enzyme-linked immunosorbent assay (ELISA). To evaluate the protective capacity of CTB-Fim2, an intraperitoneal or intranasal mouse immunization schedule was performed with 50 μg of CTB-Fim2. Recombinant (rFim2) or purified (BpFim2) Fim2, CTB, and phosphate-buffered saline (PBS) were used as controls. The results showed that mice immunized with BpFim2 or CTB-Fim2 intraperitoneally or intranasally presented a significant reduction in bacterial lung counts compared to control groups (P < 0.01 or P < 0.001, resp.). Moreover, intranasal immunization with CTB-Fim2 induced significant levels of Fim2-specific IgG in serum and bronchoalveolar lavage (BAL) and Fim2-specific IgA in BAL. Analysis of IgG isotypes and cytokines mRNA levels showed that CTB-Fim2 results in a mixed Th1/Th2 (T-helper) response. The data presented here provide support for CTB-Fim2 as a promising recombinant antigen against Bordetella pertussis infection.